The Description of Students’ Creativity and Motivation in Physics: Introducing Madurese Local Wisdom “Karapan Sapi” as Ethnophysics Learning Media - Mirsa, Fara Raditya; Islamiyah, Ahla Nurul; Rizki, Iqbal Ainur; Saputri, Aulia Dwi; Ramadani, Riski; Habibulloh, Muhammad (Universitas Muhammadiyah Sidoarjo, 2023)
Creative thinking skills are one of the important abilities in the 21st century because they play an important role for individuals in approaching the solution of daily life problems. The importance of creativity in education demands an effort to foster this skill in various learning activities. However, teachers tend to still not apply learning activities that can train creativity by design. Ethnoscience-based learning based on the local wisdom of Madura karapan sapi can be an alternative solution in overcoming these problems. Therefore, this research aims to describe students’ creativity and motivation as well as explore the potential of karapan sapi as a physics learning media. The research design used was mixed-method exploratory with quantitative methods of one-shot case study and survey to 37 students of SMAN 3 Sidoarjo combined with interviews and observations to the owner of the bull race. The results showed that students still have a creativity score of 9.51 or at low criteria. Meanwhile, more than 75% of students claimed to lack motivation to learn physics. To remediate this, the application of cow race tradition in physics learning makes students closer and feel more contextualized in understanding physics concepts in order to increase their creativity and motivation.